Resistance of Phaseolus vulgaris genotypes to Zabrotes subfasciatus (Coleoptera: Chrysomelidae: Bruchinae): categories and mechanisms - Boiça Júnior, Arlindo Leal [UNESP]; Eduardo, Wellington Ivo [UNESP]; de Moraes, Renato Franco Oliveira [UNESP]; Louvandini, Helder; Di Bello, Mirella Marconato [UNESP]; Carbonell, Sérgio Augusto Morais (Springer Nature, 2021)
Information on Phaseolus vulgaris L. resistance categories and mechanisms to the Mexican bean weevil Zabrotes subfasciatus Boheman (Coleoptera: Chrysomelidae: Bruchinae) is important for breeding and subsequent commercialization of improved P. vulgaris genotypes. Using resistant genotypes in the bruchid beetles control may reduce insecticide applications, environmental risks, and production costs. Therefore, the objective of this study was to evaluate antixenosis and antibiosis of P. vulgaris genotypes to Z. subfasciatus and the relation of bromatological components on resistance. Free- and no-choice tests were carried out in a climate-controlled room (temperature 25 ± 1 °C, relative humidity 70 ± 10%, and 12:12 h light:dark photoperiod). Host selection for oviposition, total and viable numbers of eggs, emerged adults, egg to adult period (life cycle), adult longevity, and dry mass consumed of Z. subfasciatus were evaluated on 10 P. vulgaris genotypes. Bean samples of P. vulgaris genotypes were subjected to a bromatological analysis to determine possible resistance mechanisms. In the oviposition antixenosis, none of the P. vulgaris genotypes showed resistance to Z. subfasciatus. Contrastingly, the genotypes Raz 59, 173, 177, 179, 283, 284, 361, and 364 showed resistance in the categories of feeding antixenosis and/or antibiosis to Z. subfasciatus. On average, these genotypes reduced the number of emerged adults in 95.9%, the dry mass consumed in 88.3%, and increased the Z. subfasciatus life cycle in 40.3% compared to susceptible genotypes (IAC Alvorada and 178). Crude protein content in the resistant genotypes was on average 10.9% higher than in the susceptible genotypes. Some proteins, such as arcelin, have antibiotic effects on bruchid beetles, indicating that a higher protein content in resistant genotypes may have been one of the mechanisms responsible for antibiosis of these genotypes to Z. subfasciatus.
Keywords: Antibiosis; Antixenosis; Fiber; Mexican bean weevils; Phenols; Tannin